Kritik Matan Hadis Dispensasi Abu Lahab dalam Bingkai Shalahuddin Al-Idlibi - Irfan Fauzi; Zulfi Fadhlurrahman; Milad Ainur Rachman (Journal of Hadith Studies, 2025)
This study critically examines Bukhari Hadith number 5101, which narrates Abu Lahab's exemption from punishment attributed to his act of freeing the slave Tsuwaibah. Methodologically, this library-based research employs the matn criticism approach developed by Shalahuddin Al-Idlibi. Primary data sources include hadith collections, while secondary data comprises various scholarly books, journal articles, Qur'anic interpretation, sirah nabawiyah, and other literature relevant to the research context. The research findings indicate that the hadith's matn does not contradict Qur’anic verses, other authentic hadiths, sirah nabawiyah, rationality, or existing historical facts, and does not have a haphazard meaning. The applied metanarrative criticism definitively confirms that the additional narrative concerning Abu Lahab’s exemption from punishment constitutes a narratorial insertion (idraj). Crucially, this insertion does not diminish the hadith’s overall authenticity, neither in its isnad nor its matn. This study particularly highlights the importance of matn criticism, an area that has historically received less academic attention compared to isnad criticism. Furthermore, it aims to foster the development of more applicable methods of matn criticism within contemporary hadith scholarship. The implications of this research are expected to both enrich existing hadith research methodologies and clarify public understanding regarding the validity of narratives about Abu Lahab’s exemption from punishment.